Reach, Receptivity, And Beliefs Associated With the Fresh Empire Campaign to Prevent and Reduce Cigarette Use Among Youth in the United States. Issue 5 (June 2022) - Guillory, Jamie; Curry, Laurel; Farrelly, Matthew; Henes, Amy; Homsi, Ghada; Saunders, McKinley; MacMonegle, Anna; Fiacco, Leah; Alexander, Tesfa; Delahanty, Janine; Mekos, Debra; Hoffman, Leah; et al.
Purpose: To determine the association between exposure to FDA's Fresh Empire tobacco public education campaign and tobacco-related beliefs. Design: Repeated cross-sectional data collection design with embedded longitudinal cohort over six data collection waves. Setting: 30 US evaluation markets. Sample: Hip Hop peer crowd-identified US youth aged 12–18 (N = 5, 378). Measures: Self-reported brand and video ad awareness (saw any ad at least sometimes) and perceived effectiveness (1–5 scale) to describe campaign awareness and receptivity. Exogenous exposure was measured using population-adjusted broadcast and digital video impressions. Tobacco-related beliefs included beliefs about smoking risks, attitudes towards tobacco-free people and lifestyles, and normative beliefs about smoking. Analysis: Descriptive analyses of awareness, receptivity, and agreement with tobacco-related beliefs. Logistic regression models to determine the relationship between broadcast and digital video impressions and beliefs. Intervention: Fresh Empire campaign. Results: The campaign generated a high level of reach (71% brand and 66% video ad awareness at final wave) and messages were well-received (across waves 3.5–4.1 mean perceived effectiveness scores). Higher broadcast television exposure was associated with increased agreement with five beliefs related to addiction/control, being a bad influence on family/friends, and cosmetic effects of smoking (breath and attractiveness) (ORs = 1.16–1.27, ( P s < .05)). Conclusion: Fresh Empire successfully reached and resonated with Hip Hop-identified youth. The campaign was associated with a limited number of targeted beliefs.